Expression of TRPV1 channels after nerve injury provides an essential delivery tool for neuropathic pain attenuation. - Zakir, H.M.; Mostafeezur, R.M.; Suzuki, A.; Hitomi, S.; Suzuki, I.; Maeda, T.; Seo, K.; Yamada, Y.; Yamamura, K.; Lev, S.; Binshtok, A.M.; Iwata, K.; et al. (Public Library of Science, 2012)
Increased expression of the transient receptor potential vanilloid 1 (TRPV1) channels, following nerve injury, may facilitate the entry of QX-314 into nociceptive neurons in order to achieve effective and selective pain relief. In this study we hypothesized that the level of QX-314/capsaicin (QX-CAP)--induced blockade of nocifensive behavior could be used as an indirect in-vivo measurement of functional expression of TRPV1 channels. We used the QX-CAP combination to monitor the functional expression of TRPV1 in regenerated neurons after inferior alveolar nerve (IAN) transection in rats. We evaluated the effect of this combination on pain threshold at different time points after IAN transection by analyzing the escape thresholds to mechanical stimulation of lateral mental skin. At 2 weeks after IAN transection, there was no QX-CAP mediated block of mechanical hyperalgesia, implying that there was no functional expression of TRPV1 channels. These results were confirmed immunohistochemically by staining of regenerated trigeminal ganglion (TG) neurons. This suggests that TRPV1 channel expression is an essential necessity for the QX-CAP mediated blockade. Furthermore, we show that 3 and 4 weeks after IAN transection, application of QX-CAP produced a gradual increase in escape threshold, which paralleled the increased levels of TRPV1 channels that were detected in regenerated TG neurons. Immunohistochemical analysis also revealed that non-myelinated neurons regenerated slowly compared to myelinated neurons following IAN transection. We also show that TRPV1 expression shifted towards myelinated neurons. Our findings suggest that nerve injury modulates the TRPV1 expression pattern in regenerated neurons and that the effectiveness of QX-CAP induced blockade depends on the availability of functional TRPV1 receptors in regenerated neurons. The results of this study also suggest that the QX-CAP based approach can be used as a new behavioral tool to detect dynamic changes in TRPV1 expression, in various pathological conditions.